COMPARATIVE EFFECTIVENESS OF SLEEPER STRETCH AND CROSS - BODY STRETCH FOR IMPROVING POSTERIOR SHOULDER TIGHTNESS, PAIN AND FUNCTION IN PATIENTS WITH ADHESIVE CAPSULITIS – A RANDOMIZED CONTROLLED TRIAL (International Journal of Physiotherapy, 2020)
Background: Adhesive Capsulitis usually involves the posterior capsule tightness, which can be stretched either by sleepers or cross-body stretch techniques. The present study aimed to compare and see the effectiveness of two stretching techniques on horizontal adduction and internal rotation range of motion along with pain and disability.Methodology: The study was conducted on 30 subjects diagnosed with adhesive capsulitis (12 females and 18 males) of age group 40-65 years and meeting the inclusion as well as the exclusion criteria. Subjects were divided into three groups- Cross body stretch group (Group 1), Sleeper Stretch group (Group 2), and Control group (Group 3) randomly. Both groups 1 & 2 received the intervention given to group 3 along with the different stretching techniques three times a week for four weeks. Clinical outcome measures were horizontal adduction and internal rotation as measured with a goniometer, pain intensity on a numeric pain rating scale, and shoulder disability with the help of shoulder pain and disability index.Result: Data was collected at baseline and after four weeks of intervention in all three groups. Data were checked for normal distribution. For non-normally distributed data, Kruskal Wallis test-Pain (p-value> 0.419) and Function (p-value>0.665) and for normally distributed data, one-way repeated measure ANOVA-Shoulder Horizontal Adduction (p-value>0.284) and Internal Rotation (p-value>0.334) was used and the p-value was fixed to < 0.05.Conclusion: Both the type of stretches were equally effective for four weeks.